Factors Of Advertising Value Through Advertising Attitude And Purchase Intention On Tik-Tok Social Media - Dinara Safina Akmalia; Erlita Ridanasti (International Journal of Economics, Business and Innovation Research, 2024)
This study focuses on analyzing how credibility, information, entertainment, and irritation in advertisements influence the attitudes and purchasing decisions of TikTok users in Indonesia. The research employs a quantitative approach and gathers data from 224 respondents who actively use TikTok. The findings indicate that advertising factors such as credibility, information, entertainment, and irritation have a positive and significant impact on attitudes and purchasing decisions. This research provides beneficial insights for marketers and entrepreneurs in formulating effective marketing strategies on TikTok.